Apelin-13 infusion salvages the peri-infarct region to preserve cardiac function after severe myocardial injury - Chung, W-J; Cho, A; Byun, K; Ge, X; Moon, EJ; Seo, H-S; Moon, E; Dash, R; Yang, PC (Elsevier, 2016)
Background: Apelin-13 (A13) regulates cardiac homeostasis. However, the effects and mechanism of A13 infusion after an acute myocardial injury (AMI) have not been elucidated. This study assesses the restorative effects and mechanism of A13 on the peri-infarct region in murine AMI model.